2022
DOI: 10.31557/apjcp.2022.23.12.4177
|View full text |Cite
|
Sign up to set email alerts
|

Immunoexpression of Tumor Infiltrating Lymphocytes(TILS) CD4 + and CD8 + in Oral Squamous Cell Carcinoma (OSCC) in Correlations with Clinicopathological Characteristics and Prognosis

Abstract: Objective: This study aimed to analyze CD4 +and CD8 + TILs in oral squamous cell carcinoma (OSCC) and to correlate it with histologic grade of malignancy and clinicopathologic data. Methods: The sample was composed of 43 archived specimens. Clinical features and histological grade of malignancy were obtained. The infiltrating intensity of CD4 +, CD8 positive cells were assessed by immunohistochemistry. One-way ANOVA was used to study the association between CD4 +, CD8 + and the grade of OSCC. The cut-off value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In this study, CD4+ and CD8+ expression was not significantly associated with clinical parameters such as age, gender, tobacco habit, or the tumor site. The results of the study were similar to those of a study by Wahbi and Manadili [ 8 ], where it was reported that CD4+ and CD8+ expression was not significantly associated with age, gender, and tobacco smoking. However, this is contrary to a study by Lequerica-Fernández et al [ 5 ], in which there were higher CD4+ and CD8+ TILs in patients without tobacco smoking and alcohol consumption.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, CD4+ and CD8+ expression was not significantly associated with clinical parameters such as age, gender, tobacco habit, or the tumor site. The results of the study were similar to those of a study by Wahbi and Manadili [ 8 ], where it was reported that CD4+ and CD8+ expression was not significantly associated with age, gender, and tobacco smoking. However, this is contrary to a study by Lequerica-Fernández et al [ 5 ], in which there were higher CD4+ and CD8+ TILs in patients without tobacco smoking and alcohol consumption.…”
Section: Discussionsupporting
confidence: 90%
“…Fang et al [22] investigated the prognostic significance of TILs in OSCC and concluded that higher CD8+ expression was associated with the absence of regional lymph node metastasis. In contrast, in the study by Wahbi and Manadili [8], CD4+ and CD8+ infiltration did not show any significant association with the TNM stage. Similarly, Mohajertehran et al [23] reported no significant association between CD4+ infiltration and the TNM stage.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…As CD4 + T cells are also crucial in the development of CD, their uncontrolled activation within the CD context may lead to the emergence of CRC [ 31 ]. Wahbi et al [ 32 ] analyzed the presence of CD4 + and CD8+ Tumor Infiltrating Lymphocytes (TILs) in oral squamous cell carcinoma (OSCC) and their correlation with malignancy grade. CD4 + TILs were more frequent in poorly differentiated specimens, while CD8+ TILs were more frequent in well-differentiated specimens.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + TILs were more frequent in poorly differentiated specimens, while CD8+ TILs were more frequent in well-differentiated specimens. The CD4 +/CD8+ ratio was higher in low-grade specimens, suggesting that CD4 + and CD4 +/CD8+ ratio are independent prognostic factors in OSCC [ 32 ]. Salama et al [ 33 ] investigated the correlation between PDL1 expression and clinicopathological parameters in endometrial cancer (EC) cases, focusing on CD4 and CD8 immune cells.…”
Section: Discussionmentioning
confidence: 99%